Innovation for All: Unleashing the Power of Assistive Technology in Special Education in Arabic-Speaking Countries - Alanazi, Mona Saleh (Journal of ICSAR, 2023)
This topical review digs into special education teachers' growing usage of Assistive Technology (AT) in Arabic-speaking countries to serve children with impairments. This study investigates AT's benefits, drawbacks, and possible applications in this educational setting by reviewing the available literature from six major academic databases, including Scopus, Web of Science, JSTOR, ERIC, Academia, and ResearchGate. The findings highlight the need for tailored and student-centered approaches to AT adoption and effective training and ongoing support for educators and students. Furthermore, the study emphasizes the potential of AT to improve academic and functional outcomes, allowing students to overcome obstacles and actively participate in their educational path. The significance of these findings for future special education research and practice is examined, laying the groundwork for further investigation of AT's influence on children with disabilities in Arabic-speaking countries. The outcomes of this review emphasize the need to implement AT in Arabic-speaking special education settings using tailored and student-centered approaches. Students with disabilities can effectively use AT solutions to enhance their learning experiences by tailoring AT solutions to specific needs. Furthermore, the study emphasizes the importance of instructor and student training and ongoing assistance. Proper training provides instructors with the skills and information they need to properly deploy AT tools, while continual support ensures that AT remains effective in the classroom.